Anthropogenic vulnerability assessment of global terrestrial protected areas with a new framework - Meng, Jiahui; Li, Yaoqi; Feng, Yuhao; Hua, Fangyuan; Shen, Xiaoli; Sheng Li; Shrestha, Nawal; Peng, Shijia; Rahbek, Carsten; Wang, Zhiheng (Biological ConservationBiological Conservation, 2023)
Protected areas (PAs) are the major conservation tool for ecosystem conservation, but function unequally in mitigating human pressures in practice. Assessing PA vulnerability caused by human pressures and its association with socioeconomic and PA characteristic factors is vital for improving conservation effectiveness and the post-2020 PA expansion. Here, using a new framework integrating the intensity and temporal changes of human pressures in PAs and their matched unprotected areas, we categorize global terrestrial PAs into four anthropogenic vulnerability levels: high (11.7 %), moderate (18.6 %) and low (21.9 %) vulnerability and wilderness (47.8 %). We find significant variations in the anthropogenic vulnerability of PAs between countries, continents, and IUCN categories. Europe has the highest proportion of high-vulnerability PAs (ca. 19.7 % of protected areas in Europe), while South America and Oceania have the highest proportions of low-vulnerability PAs and wilderness PAs, respectively (33.2 % and 75.0 % respectively). The vulnerability of PAs is not significantly associated with socioeconomic factors at the country level, which might reflect the trade-offs between positive and negative outcomes of development. With a new framework that integrated four significant factors for anthropogenic vulnerability assessment, this study demonstrates that global PAs have different anthropogenic vulnerability levels and suggest that some PAs function effectively in mitigating human pressures despite currently intense human pressures within them. Our results also suggest that future evaluations on the conservation status should pay attention not only to PA coverage but also to the anthropogenic vulnerability levels within PAs to achieve higher conservation effectiveness.
Keywords: Anthropogenic vulnerability; Conservation assessment; Human modification; Human pressure; Protected area; Socioeconomic factor